Investigating the molecular mechanism of iguratimod act on SLE using network pharmacology and molecular docking analysis - Zeng, Huiqiong; Chen, Shuai; Lu, Xiaoping; Yan, Zhenbo (Frontiers in Bioinformatics, 2022)
Objective: Iguratimod (IGU) is a novel small disease-modifying compound widely used in Asia for the treatment of rheumatic diseases. IGU is a methane sulfonanilide. We applied network pharmacology to investigate the pharmacological mechanisms of IGU act on SLE. Methods: We used PharmMapper, UniProt, and OMIM databases to screen the potential targets of IGU, and the SLE-related disease targets were predicted. Hub target genes among the intersections of the potential targets (IGU) and related genes (SLE) were validated using the PPI network generated by the String database. GO and KEGG enrichment analyses were carried out using the David online platform. Finally, the molecular docking of hub targets and their corresponding compounds were completed through AutoDock Vina and PyMOL software for visualization. Result: A total of 292 potential targets of IGU, 6501 related disease targets of SLE, and 114 cross targets were screened from the aforementioned database. Network topology analysis identified 10 hub targets, such as CASP3, AKT1, EGFR, MMP9, and IGF1. GO enrichment analysis mainly focuses on the negative regulation of the apoptotic process and signal transduction. KEGG enrichment analysis illustrated that the PI3K-AKT signaling pathway, MAPK signaling pathway, and FoxO signaling pathway might play a significant role in the pharmacological mechanisms of IGU act on SLE. Molecular docking confirmed that the IGU ligand had strong binding activity to the hub targets. Conclusion: This study based on network pharmacology and molecular docking validation preliminarily revealed the protein targets affected by IGU acting on SLE through, and explored potential therapeutic mechanism role of IGU in SLE treatment by multi pathways.